Pharmacological Profile and Therapeutic Potential of Sungkai Plant (Peronema canescens Jack.): An Emerging Indonesian Herbal Medicine - Yasmiwar Susilawati; Sri Adi Sumiwi; Okta Nama Putra; Asep Kokom (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
This study aimed to summarize the pharmacological activities of the sungkai plant (Peronema canescens Jack.) as a potential Indonesian herbal medicine. A literature review was conducted using Google Scholar and Scopus, with keywords such as "pharmacology," "activity," "sungkai," and "Peronema canescens." Inclusion criteria were articles with these keywords, published between 2014 and 2024, in English or Indonesian. Exclusion criteria were review articles, articles not related to sungkai plants, and in vitro and in vivo studies not available in full text. The study identified seven pharmacological activities of the sungkai plant: antioxidant, antibacterial, analgesic, antidiabetic, antihyperuricemic, anti-inflammatory, and immunomodulatory. The antioxidant activity was demonstrated using Thin Layer Chromatography (TLC) and IC50 values. The antibacterial activity was shown through bacterial growth inhibition using the Kirby-Bauer disk diffusion method. The analgesic activity was tested using the writhing test and Hot Plate methods. The antidiabetic activity was studied with alloxan induction method. Overall, the sungkai plant exhibits various pharmacological activities, suggesting its potential as an herbal medicine for treating various diseases.